مستوي معرفة معلمي التعليم العام باضطراب ضعف الانتباه وفرط الحركة (ADHD) في المرحلة الابتدائية في دولة الكويت - السعيدي، أحمد محسن; الحربي، حمدان عوض فراج (جامعة البحرين - مركز النشر العلمي, 2017)
The purpose of this study are to investigate the level of general education teachers’ knowledge of attention deficit hyperactivity disorder (ADHD) at primary school in the State of Kuwait, to explore the effect of gender and subject. The sample of the study consisted of 250 male and female teachers in the primary school at Al-Ahmadi and Jahra Educational Area. The researcher administrated Bruna (2004) scale translated by the authors, and then used suitable statistical procedures. The results of the study showed that the level of the teachers’ general knowledge of attention deficit hyperactivity disorder (ADHD) was low as the mean totalled 48.9% and there were no significant statistical differences between male and female teachers on the level of knowing this disorder. Furthermore, the findings showed that Arabic language teachers had knowledge about this disorder compared to other majors.
هدفت الدراسة الحالية إلى التعرف على مستوى معرفة معلمي التعليم العام باضطراب ضعف الانتباه وفرط الحركة(ADHD) في المرحلة الابتدائية في دولة الكويت، والكشف عن أثر النوع والمادة الدراسية، تكونت عينة الدراسة من (250) معلما ومعلمة في المرحلة الابتدائية لإدارة منطقتي الأحمدي والجهراء التعليميتين، واستخدم الباحثان اختبار من إعداد (Bruna, 2004) تعريب وتقنين الباحثين، استخدمت الأساليب الإحصائية المناسبة لذلك. وأشارت النتائج إلى أن مستوى معرفة معلمي التعليم العام باضطراب ضعف الانتباه وفرط الحركة (ADHD) كانت منخفضة إذ بلغ المتوسط الحسابي لمستوى المعرفة (9,30) بنسبة (48,9%) كما أشارت النتائج إلى أنه لا توجد فروق ذات دلالة إحصائية بين المعلمين والمعلمات في مستوى المعرفة حول هذا الاضطراب، كما أشارت النتائج إلى أن معلمي اللغة العربية هم أكثر مستوى معرفة بهذا الاضطراب من المواد الأخرى.
Keywords: فرط الحركة; ضعف الانتباه; الكويت; التعليم العام; المرحلة الابتدائية